1996
DOI: 10.1042/bj3160143
|View full text |Cite
|
Sign up to set email alerts
|

Subunit structure of vacuolar proton-pyrophosphatase as determined by radiation inactivation

Abstract: Vacuolar proton-pyrophosphatase (H(+)-PPase) of mung bean seedlings contains a single kind of polypeptide with a molecular mass of approx. 73 kDa. However, in this study, a molecular mass of approx. 140 kDa was obtained for the purified vacuolar H(+)-PPase by size-exclusion gel-filtration chromatography, suggesting that the solubilized form of this enzyme is a dimer. Radiation inactivation analysis of tonoplast vesicles yielded functional masses of 141.5 +/- 10.8 and 158.4 +/- 19.5 kDa for PP1 hydrolysis activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Proton translocation of submitochondrial particles was measured as fluorescence quenching of acridine orange (excitation 495 nm, emission 530 nm) by a Hitachi F‐4000 fluorescence spectrophotometer as previously described [4]. The reaction mixture (2 ml) contained 10 mM HEPES–Tris (pH 7.5), 50 mM KCl, 250 mM sucrose, 5 mM MgSO 4 , 1 mM EGTA, 5 μM acridine orange, and 50 μg submitochondrial particles.…”
Section: Methodsmentioning
confidence: 99%
“…Proton translocation of submitochondrial particles was measured as fluorescence quenching of acridine orange (excitation 495 nm, emission 530 nm) by a Hitachi F‐4000 fluorescence spectrophotometer as previously described [4]. The reaction mixture (2 ml) contained 10 mM HEPES–Tris (pH 7.5), 50 mM KCl, 250 mM sucrose, 5 mM MgSO 4 , 1 mM EGTA, 5 μM acridine orange, and 50 μg submitochondrial particles.…”
Section: Methodsmentioning
confidence: 99%
“…Irradiation was performed with a 60 Co irradiator (approximately 1.11×10 6 GBq) and the dose rate was 7.00×10 -3 Mrad s -1 determined as previously described (Pan et al 1987, Wang et al 1988, Ma et al 1993, Tzeng et al 1996, Jiang et al 2000, Wu et al 2004. Internal standardization of radiation exposure was carried out with G 6 PDH.…”
Section: Sds-page and Autoradiographymentioning
confidence: 99%
“…Highly purified H + -PPase reconstituted into proteoliposomes exhibits the H + -translocating activity (Sato et al 1994). The purified H + -PPase consists of a single polypeptide and forms a functionally active homodimer within the membrane (Maeshima 1990, Sato et al 1991, Tzeng et al 1996. Analysis of cDNAs encoding the H + -PPases from Arabidopsis thaliana and other plants has revealed that the H + -PPase consists of about 770 amino acid residues and has 12 to 15 putative membrane-spanning regions , Tanaka et al 1993, Zhen et al 1997.…”
mentioning
confidence: 97%